CAUSALITY AND COINTEGRATION AMONG STOCK MARKET INDICES: A STUDY OF DEVELOPED MARKETS WITH SENSEX - A Joshi, Nisarg; Mehta, Dhyani; Patel, Bhavesh; Patel, Nikunj (International Journal of Accounting & Finance Review, 2021)
The aim of this paper is to examine the existence of degree of interdependence between Sensex and various stock markets of the American and European regions. The study attempts to analyse the dynamic interactions among 22 global indices. The daily closing prices of indices were obtained from the respective stock exchange websites from January 2005 to May 2018.  The normality, stationarity, and causality of the time series were evaluated in the first section using statistical techniques such as the Jarque-Bera statistic, ADF test, and Granger Causality test. The second part of the approach focused on analysing the interdependencies of various stock markets, determining the degree of association, and measuring market efficiency using techniques such as Johansen's Cointegration test, Cross-Correlation test, and Hurst Exponent. The results indicate that there is a significant amount of interdependence between stock markets. It was also observed that there is an association between markets. This study also found bi-directional as well as uni-directional causality among the stock market indices. The study found that interdependence of markets leads to improvements in short-term as well as long-term returns/gains for investors possibly due to international portfolio diversification if there are stronger co-movements of prices across the markets.JEL Classification Codes: G15, F15, F21.